The Knowledge of Values and the Fragility of Democracy - Roberta De Monticelli (University of Bologna, 2020)
Three claims are discussed in this paper, concerning Education, Politics, and Phenomenology. The very foundations of a humanistic education are to be found in a radical reform of the theory of reason, which should involve emotional sensitivity along with critical thought and the passion for truth. Only educated citizens can counteract the fragility of contemporary democracy, due to its allegedly essential link to value relativism. Phenomenology, a method for philosophical research born as a response to the shipwreck of reason in the first half of last century, can develop axiology and the theory of value experience into a renewed theory of practical reason, becoming a key against moral, civic and political skepticism that hampers a necessary reawakening of citizenry to the arduous task of creating a veritable supranational democracy.